Online Shopping in the Perspective of the Book of Hāsyiyah As-Shaykh Ibrāhīm Al-Bayjūri - Tajun Yuhsinun; Purwanto Purwanto; Ahmad Mustofa; M. Pudail (Universitas Muhammadiyah Magelang, 2022)
This study aims to describe as well as complement previous research on the terms and pillars of online sale and purchase, especially those listed in the Book of Hāsyiyah As-Shaykh Ibrāhīm Al-Bayjūri. This study uses a qualitative analysis on the practice of online shopping at the Darul Kutub Wasatiya store as reviewed by the Book of Hāsyiyah As-Shaykh Ibrāhīm Al-Bayjūri. This study uses primary data from the Book of Hāsyiyah As-Syaikh Ibrāhīm Al-Bayjūri and secondary data from the Book of Fathul Qorīb Al-Mujīb and other literacy that discusses online shopping contracts. The results of this study indicate that the practice of online sale and purchase does not conflict with Islamic law, even though methodologically there are differences in transactions, especially in fulfilling the terms of ijab and kabul.